2000
DOI: 10.7326/0003-4819-132-9-200005020-00005
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia, Cerebral Edema, and Noncardiogenic Pulmonary Edema in Marathon Runners

Abstract: In healthy marathon runners, noncardiogenic pulmonary edema can be associated with hyponatremic encephalopathy. The condition may be fatal if undiagnosed and can be successfully treated with hypertonic NaCl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
231
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(236 citation statements)
references
References 13 publications
0
231
0
5
Order By: Relevance
“…In this study, the incidence of NSAID use in athletes was 30%, and NSAID use was highly associated with the development of hyponatremia (P ϭ 0.0002), as well as higher plasma potassium and creatinine levels. Several other, smaller studies and case reports also have suggested a potentiating role for NSAID use (11,12,52). Therefore, the role of NSAID in the development of EAH remains controversial but in some runners likely is a potentiating factor.…”
Section: Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, the incidence of NSAID use in athletes was 30%, and NSAID use was highly associated with the development of hyponatremia (P ϭ 0.0002), as well as higher plasma potassium and creatinine levels. Several other, smaller studies and case reports also have suggested a potentiating role for NSAID use (11,12,52). Therefore, the role of NSAID in the development of EAH remains controversial but in some runners likely is a potentiating factor.…”
Section: Risk Factorsmentioning
confidence: 99%
“…During this period, military recruits were encouraged to ingest 1.8 L of fluid for every hour they were exposed to temperatures above 30°C (30). At least four other deaths have been attributed to EAH in the United States (5,10,11,26,31). It is interesting that two of these deaths occurred in doctors (31).…”
Section: Incidencementioning
confidence: 99%
See 2 more Smart Citations
“…EAH can be severe and life threatening as a result of cerebral edema and noncardiogenic pulmonary edema. 33,94 Prevention is paramount. Guidelines for appropriate fluid ingestion during marathons are available.…”
Section: Siadhmentioning
confidence: 99%